Updates in the Diagnosis and Treatment of Vasculitis - Sakkas, Lazaros I.; Katsiari, Christina (IntechOpen, 2013)
Vasculitis, an inflammation of blood vessels, can be idiopathic or secondary to other conditions. Infections may also mimic idiopathic vasculitis, and the differential diagnosis is of paramount importance for the practicing physician. Vasculitides are not rare diseases. In fact, some vasculitides, such as giant cell arteritis, cutaneous vasculitis, and ANCA-associated vasculitis are relatively common in everyday practice. Vasculitis may rapidly lead to organ failure, and put patient's life in danger. Therefore, physicians of different specialties should diagnose vasculitis early, because early institution of treatment is crucial for the favorable outcome. In recent years progress has been made in the pathophysiology and treatment of vasculitis. This book reflects all new advances in pathogenetic mechanisms, diagnosis, and treatment of different types of vasculitis. The international panel of authors helps in achieving a balanced view on different aspects of vasculitis.